The book of hope : [large type] a survival guide for trying times - Goodall, Jane, 1934-; Abrams, Douglas Carlton; Hudson, Gail (Thorndike Press large print nonfiction series., 2022)
"Jane Goodall, the world's most famous living naturalist, and Doug Abrams, internationally bestselling author, explore one of the most sought after and least understood elements of human nature: hope. Told through stories from a remarkable career and fascinating research, The Book of Hope is a deeply personal conversation. For the first time, Jane tells the story of how she became a messenger of hope: from living through World War II, to her years in Gombe, to realizing she had to leave the forest to travel the world as an advocate for environmental justice. There is still hope, and this book will help guide us to it."--Back cover.